How Robust Is Local Knowledge? The Role of Pranata Mangsa in Rice Production - Budiyoko, Budiyoko; Verrysaputro, Exwan Andriyan; Sunendar, Sunendar (Program Pascasarjana Universitas Sriwijaya, 2025)
The Bonokeling indigenous community of Banyumas District is still insisting on continuing its various traditions and local wisdom within various phases of life. One form of local wisdom possessed by the people of Bonokeling is the pranata mangsa, a calendrical system based on the apparent motion of the sun, which is widely used by Javanese farmers to determine planting times for agricultural commodities. This research was conducted in a bid to analyze the application of pranata mangsa and its impact on rice yield. In that respect, this qualitative-quantitative study uses primary data collected from interviews conducted among 50 farmers within the Bonokeling community and secondary data taken from the previous research and publications by related institutions. Data analysis used in the Wilcoxon signed-rank test. The result shows that there is no significant difference in the rice produced between farmers who used pranata mangsa and those who did not. This might probably be explained by increased uncertainty of the seasons due to climate change.